Answer:
me niether
Step-by-step explanation:
lol
It is an enlargement because the scale factor is 2 and a half
(x+5)(x-5)
= x^2 - 5x + 5x - 25
= x^2 - 25
(5x+3)(5x-3)
= 25x^2 - 15x + 15x - 9
= 25x^2 - 9
do you see the pattern? both the coefficient on x and constant multiply together to make a perfect square and the middle term, also known as "b" term cancels out leaving a binomial
Answer:
N=8
Step-by-step explanation:
6N=48
Divide by 6 both sides
6N/6=48/6
N=8
Answer:
A=2
Step-by-step explanation: